PERSEPSI PENGUNJUNG TERHADAP DAYA TARIK WISATA DANAU TAJWID KECAMATAN LANGGAM KABUPATEN PELALAWAN - Purwanto, Purwanto; Sadjati, Emy; Insusanty, Enny (Fakultas Kehutanan Universitas Lancang Kuning, 2019)
This study aims to find out the Visitor Perception of Lake Tajwid Tourism Attraction in Langgam District, Pelalawan Regency in 2018 which consists of 4 indicators: attractions, accessibilities, amenities, and ancillary services (supporting facilities). This type of research is quantitative research, with a total sample of 100 people using the Nonprobability Sampling technique. Data collection uses a questionnaire based on the Likert Scale. Furthermore, the data were analyzed through descriptive analysis with an assessment categorization method based on the average score and percentage assessment. The results of the study showed that visitors' perceptions of Lake Tajwid Travel Attractions were based on each indicator, namely: (1) Attractions were categorized as good with an average percentage of 80%, (2) Accessibility was categorized as poor with an average percentage of 42% Facilities are categorized very well with an average percentage of 87%, (4) Supporting facilities are categorized quite well with an average percentage of 55%.